2015
DOI: 10.1099/mgen.0.000032
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule real-time sequencing of Xanthomonas oryzae genomes reveals a dynamic structure and complex TAL (transcription activator-like) effector gene relationships

Abstract: Pathogen-injected, direct transcriptional activators of host genes, TAL (transcription activator-like) effectors play determinative roles in plant diseases caused by Xanthomonas spp. A large domain of nearly identical, 33–35 aa repeats in each protein mediates DNA recognition. This modularity makes TAL effectors customizable and thus important also in biotechnology. However, the repeats render TAL effector (tal) genes nearly impossible to assemble using next-generation, short reads. Here, we demonstrate that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 65 publications
3
100
0
Order By: Relevance
“…Bioinformatic searches of the sequence information currently available for X. oryzae indicated that the GA biosynthetic operon is present in Xoc, but not those for the closely related and other major pathovar X. oryzae pv. oryzae (Xoo) whose genomes have been fully sequenced (Lee et al, 2005;Ochiai et al, 2005;Salzberg et al, 2008;Booher et al, 2015;Quibod et al, 2016). In Xoc, examination of the available genome sequences (Bogdanove et al, 2011;Wilkins et al, 2015) revealed that the GA biosynthetic operon is flanked by multiple insertion sequence (IS) elements.…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatic searches of the sequence information currently available for X. oryzae indicated that the GA biosynthetic operon is present in Xoc, but not those for the closely related and other major pathovar X. oryzae pv. oryzae (Xoo) whose genomes have been fully sequenced (Lee et al, 2005;Ochiai et al, 2005;Salzberg et al, 2008;Booher et al, 2015;Quibod et al, 2016). In Xoc, examination of the available genome sequences (Bogdanove et al, 2011;Wilkins et al, 2015) revealed that the GA biosynthetic operon is flanked by multiple insertion sequence (IS) elements.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenomic tree of Indian Xoo strains along with other Asian strains [XOOK59, XOOM60, XOOP61, PXO8662, PXO8363, XO35933 (NCBI accession number: AXVI00000000), XOC_BLS25664], African strains (XOO_NAI865, XOC_MAI1065, XOC_CFBP734262) and the USA strains (X8-1A56, X11-5A56) was obtained using 31 phylogenomic marker genes14, extracted from each genome and concatenated. Mega 7.0 was used for obtaining multiple sequence alignment of the concatenated sequences as well as to obtain phylogenetic tree66.…”
Section: Methodsmentioning
confidence: 99%
“…The recent sequencing and resequencing of several X. oryzae strains indeed revealed a dynamic genome structure and an important plasticity in TAL effector genes through HGT, duplication, and recombination (19). More generally, broad sequence analyses of genes coding for pathogenicity determinants together with their genomic environment will help to determine not only their functions but also the mechanisms by which they appear and evolve in a given population (88,124).…”
Section: Exploring Genome Plasticity and Effector Evolutionmentioning
confidence: 99%